Mechanical effects of carbon in iron - Nabarro, F.R.N. (Physical Society, 1948)
Snoek has shown that when carbon atoms move from one possible set of interstitial sites in the lattice of a-iron to another set they cause shear strains. Cottrell has shown that the stress around a dislocation may be relieved by the migration of solute atoms in its neighbourhood, and that the dislocation is then bound to its present position. By combining these theories with the usual theory of age-hardening it is possible to explain the existence of a yeield point, quench aging, strain aging, delayed yield and blue brittleness as consequences of the presence of carbon in iron. A rough quantitative theory of the time-aging effects is given, and shown to agree with experiment. The need for further experiment is emphasized.
Keywords: carbon; carbon in iron